Peran Guru Bahasa Arab dalam Memotivasi Peserta Didik Kelas VIII MTs Muhzirah Galesong Selatan dalam Proses Pembelajaran Menggunakan Google Classroom di Masa Pandemi Covid-19 - Saharudin (Dahzain Nur, 2021)
This paper describes the Role of Arabic Language Teachers in Motivating Class VIII Students of MTs Muhzirah Galesong Selatan in the Learning Process Using Google Classroom during the Covid-19 Pandemic. The main problem revealed in this paper is how the role of Arabic language teachers in motivating students in the learning process using Google Classroom during the covid-19 pandemic is. The method used in this research is qualitative research. The informants in this study were Arabic teachers and 15 students of class VIII. The results of the research are the role of Arabic language teachers in learning using google classroom, namely creating active, creative, and fun learning in various ways, giving rewards to active students, creating an effective learning atmosphere and providing motivation using positive words including you are great. The role of the Arabic language teacher in motivating students to use google classroom is very helpful to foster interest in learning even though it is done online but is not an obstacle for class VIII students.